Impact of the financial crisis in the Kurdistan Region on the private industrial sector (Bazian-Lazarj cement factory) as an example for the period (2011-2017) - Iman Ibrahim Ismail; Lava Aras (The Scientific Journal of Cihan University– Sulaimaniya, 2019)
It is known that the financial crises is one of the problems facing all countries, whether developed or developing, and that the Iraqi economy and the Kurdistan region is not far from the problems and crises and because of some internal and external factors, the financial crises in the Kurdistan region reflected on all economic sectors and including the industrial sector. The main objective of this study is to explain the impact of the financial crises in Kurdistan region on the (cement plant Bazian –Lavarge) , by presenting the factors and effects resulting from this crises , and the impact of this crises were determined on the productivity of the laboratory and the number of its workers (Descriptive ) based on data and information for the period (2011-2017).From the conclusion reached ,the financial crises has had a negative impact on investment and the industrial sector , Including the Bazian –Lavarge cement plant .this crises has led to a decreased plant .This crises has led to a decrease in the number of workers . Finally, the research evaluated some of the most important proposals .The regional government must initiate real reform to address economic problems and crises.